2011
DOI: 10.1055/s-0031-1296746
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence of Two Lithium Formulations in Healthy Volunteers

Abstract: All 90% and 95% confidence intervals were inside the limits defined by the FDA Guidance for Industry (80%-125%) and thus stated that test and reference formulation may be accepted as bioequivalent, with regard to both, maximum exposure and extent of bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…CL of carbonate lithium is mainly determined by the renal function of the subject and is less dependent on the parameter calculation method. The CL of lithium in healthy Chinese male subjects was mostly consistent with previously reported data in non-Chinese subjects [10]. A bioequivalence study of 2 lithium carbonate formulations carried out in Brazil reported a mean lithium AUC inf value of 25.22 mg * h/L after oral administration of a 300 mg dose, which was calculated by a non-compartment method using [10].…”
supporting
confidence: 86%
“…CL of carbonate lithium is mainly determined by the renal function of the subject and is less dependent on the parameter calculation method. The CL of lithium in healthy Chinese male subjects was mostly consistent with previously reported data in non-Chinese subjects [10]. A bioequivalence study of 2 lithium carbonate formulations carried out in Brazil reported a mean lithium AUC inf value of 25.22 mg * h/L after oral administration of a 300 mg dose, which was calculated by a non-compartment method using [10].…”
supporting
confidence: 86%